FEMALE INFERTILITY - Kurbaniyazova Madina Zafarjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
If a woman has never become pregnant despite regular unprotected sexual intercourse, she has primary infertility. If she has had at least one pregnancy, regardless of how it ended (childbirth, abortion, miscarriage, ectopic pregnancy), subsequent infertility is considered secondary. In their records, doctors often use Roman numerals to indicate these types of infertility: infertility I - primary, infertility II - secondary. Absolute female infertility means that the possibility of becoming pregnant naturally is completely excluded. This situation may arise, in particular, as a result of removal or congenital absence of the uterus, fallopian tubes or ovaries. Let us now move on to a more detailed account of the most common causes or forms of infertility.